2020
DOI: 10.1007/s40430-020-02567-0
|View full text |Cite
|
Sign up to set email alerts
|

A study on wire and arc additive manufacturing of low-carbon steel components: process stability, microstructural and mechanical properties

Abstract: Among metal-based additive manufacturing, wire and arc additive manufacturing is receiving increasing attention for the production of components with medium to large dimensions. In the current research, the production of low-carbon steel thin-walled components by wire and arc additive manufacturing was addressed. Firstly, the influence of two depositing direction strategies on the wall shape was investigated. Subsequently, the effect of heat input on the shape stability and the microstructure evolution of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…These barriers relate, to a large extent, to the scarcity of test data on the mechanical properties and structural performance of additively manufactured materials [12,13,14]. In light of this, there has recently been a growing number of research groups investigating the microstructural and mechanical properties of different WAAM materials, including lowalloy steels [15,16,17,18,19] and various stainless steel alloys [20,21,22,23,24,25,26,27]. The aforementioned studies have revealed a degree of anisotropy in the behaviour of WAAM stainless steel material, i.e.…”
Section: Torchmentioning
confidence: 99%
“…These barriers relate, to a large extent, to the scarcity of test data on the mechanical properties and structural performance of additively manufactured materials [12,13,14]. In light of this, there has recently been a growing number of research groups investigating the microstructural and mechanical properties of different WAAM materials, including lowalloy steels [15,16,17,18,19] and various stainless steel alloys [20,21,22,23,24,25,26,27]. The aforementioned studies have revealed a degree of anisotropy in the behaviour of WAAM stainless steel material, i.e.…”
Section: Torchmentioning
confidence: 99%
“…Essential attributes for an AM component are the resulting mechanical properties of the final product. These properties depend substantially on the thermal history of the material and relate with the microstructure, toughness, and the material [1,12,13]. For additive manufacturing, the knowledge of multilayer welding can be adapted with a few modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previously mentioned studies have selected the process variables (e.g., the arc voltage, welding current, and wire-feed speed) based on the suggestion of the wire manufacturers for conventional welding or based on several tests, while the WADED process is very different from welding. In WADED processes, the quality and geometry of weld beads (e.g., stable and smooth shape and less spatter) notably affect the process stability and the appearance of as-fabricated components [22][23][24][25]. Therefore, this study aims to explore the relationship between the process variables {C, U, and V} and the geometrical characteristics of weld beads {BW, BH, and MPL} and identify optimal process parameters that produce weld beads with expected geometrical properties.…”
Section: Introductionmentioning
confidence: 99%